2015
DOI: 10.1080/08897077.2014.962722
|View full text |Cite
|
Sign up to set email alerts
|

Medicine Resident Preparedness to Diagnose and Treat Substance use Disorders: Impact of an Enhanced Curriculum

Abstract: An enhanced SUDs curriculum for medicine residents increased self-perceived preparedness to diagnose and treat SUDs and educational quality ratings. However, there was no significant change in knowledge. Implementation of a more comprehensive curriculum and evaluation at other sites are necessary to determine the ideal SUD training model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
1
22
1
Order By: Relevance
“…Ratings of the quality of instruction have been related to perceptions of preparedness to provide treatment. An enhanced curriculum increased perceptions of preparedness to diagnose and treat and educational quality ratings (Wakeman, Pham-Kanter, Baggett & Campbell, 2014 ). Further research is required on the actual content and quality of the curricula offered in the different areas across universities.…”
Section: Discussionmentioning
confidence: 99%
“…Ratings of the quality of instruction have been related to perceptions of preparedness to provide treatment. An enhanced curriculum increased perceptions of preparedness to diagnose and treat and educational quality ratings (Wakeman, Pham-Kanter, Baggett & Campbell, 2014 ). Further research is required on the actual content and quality of the curricula offered in the different areas across universities.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Despite high rates of opioid prescribing, the majority of primary care clinicians receive little or no training during medical school and residency in prescribing opioids or managing substance use disorders. [7][8][9] As a result, few primary care clinicians feel prepared to screen for, diagnose, and treat prescription medication misuse. [10][11][12][13][14] In recent years, a growing number of resources have been released to assist clinicians with managing opioid prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread integration of substance use disorder care and competencies into graduate medical education is needed [17] and few studies have reported on patient [10, 1821] or provider outcomes [10, 2224]. A recent review of graduate medical education models of OUD training found that only 29% of interventions included explicit training in providing medications for OUD (i.e.…”
Section: Introductionmentioning
confidence: 99%